A systematic study on Zn(II)-Iminocarboxyl complexation applied in supramolecular PDMS networks. (26th May 2022) - Mo, Jiaheng; Wu, Weijian; Shan, Shijie; Wu, Xionghui; Li, Danni; Li, Rui; Lin, Yaling; Zhang, Anqiang
Abstract: Metal-ligand coordination was used to construct supramolecular elastomers with self-healing ability and excellent mechanical properties. In this study, novel iminocarboxyl-functionalized polysiloxanes (PDMS-Iminocarboxyl) was synthesized through amine-functionalized polysiloxanes (PDMS-NH2 ) with acrylic acid by aza-Michael addiction based on 1 H NMR and FTIR spectroscopy. The incorporation of zinc ions into the PDMS-Iminocarboxyl as chemical crosslinks could essentially improve the thermal and mechanical properties because of highly dynamic Zn(II)-iminocarboxyl complexation. The stoichiometric ratio of [Zn 2+ ]/[COOH] were determined by NMR titration. Furthermore, the presence of dynamic Zn(II)-iminocarboxyl equilibrium could allow a degree of strain sensitivity upon various stretching rates based on tensile experiments and rheological analysis. From the DMA and rheological analysis, modulus transition of PDMS-Iminocarboxyl@Zn x networks was closely related to the association-dissociation of Zn(II)-iminocarboxyl complexation. Besides, DFT calculations further provided the optimized configuration of metal-ligand complex according to the bond-valence-bond-length correlations. Graphical abstract: Image 1 Highlights: Supramolecular polysiloxanes elastomers are prepared by integration of Zn 2+ in PDMS-Iminocarboxyl. Dynamic reversible Zn(II)-iminocarboxyl complexation contributed to self-healing and reprocessing ability. Achieving comprehensive mechanical properties, including tensile toughness up to 45.4 MJ/m 3 . Density functional theory (DFT) calculations revealed the optimized configuration.